Thomas & the trainmaster [videorecording (DVD)] - Bransom, Phil; Coker, Steve; Henninger, Robert; Nelson, Elijah; Nelson, Daniel; Berkshire, Ayanna; Biesanz, Michael (InFuse Releasing, 2025)
The quiet town of Willamette is in danger as the ruthless Ms. Fisk plans to demolish the beloved Children's Hospital and build a Tires-to-Energy power plant in its place. But hidden in the miniature tracks of Jeremiah Wilson's model trains lies a clue to a century-old treasure. When four brave kids discover it, they're transported through a mysterious train tunnel back to the 1890s where they must unravel the mystery, find the gold, and return in time to stop Fisk and save their town.